Electronic control systems for bionic prostheses based on microcontroller platforms - Makovii, V.; Maryna Muntian (ХНУРЕ, 2026)
this paper presents the design and investigation of an electronic control system for an upper-limb bionic prosthesis based on the STM32 microcontroller platform and electromyographic (EMG) sensors. The proposed system provides acquisition, amplification, filtering, analog-to-digital conversion, and digital processing of muscle bioelectric signals to generate control commands for prosthetic actuators. The hardware architecture, signal conditioning chain, and embedded processing algorithm are described in detail. A multi-channel EMG approach combined with digital signal processing and pattern classification is used to achieve intuitive and reliable control of prosthetic movements. The results show that the integration of electronics, applied mathematics, physics of bioelectric phenomena, and biomedical engineering significantly improves the accuracy, robustness, and usability of bionic prostheses for rehabilitation.
Keywords: bionic prosthesis; EMG sensor; electronic control system; signal processing; rehabilitation engineering